Influence of ultrasound application on both the osmotic pretreatment and subsequent convective drying of pineapple (Ananas comosus). (June 2017) - Corrêa, J.L.G.; Rasia, M.C.; Mulet, A.; Cárcel, J.A.
Abstract: Ultrasound application represents an alternative means of improving heat and mass transfer. This study explored the combined application of ultrasound (US) during both the osmotic dehydration (OD) pretreatment and the convective drying of pineapple. For that purpose, fresh and pretreated samples (20 or 40 min, with (55.5 kW/m 3, 40 kHz) and without ultrasound application) in an osmotic solution of sucrose (40% w /w) were dried (40 °C and 70 °C) with (21.8 kHz, 31 kW/m 3 ) and without ultrasound application. A diffusion model permitted to quantify the influence of the factors studied (time of pretreatment, ultrasound application during pretreatment, drying temperature and ultrasound application during drying) in drying kinetics. The increase in drying temperature and the application of ultrasound during drying significantly accelerated the drying process by reducing both the internal and the external mass transport resistance. On the contrary, the osmotic pretreatments reduced the drying rate by increasing the external resistance. Highlights: Ultrasound intensifies mass transfer in the osmotic pretreatment and drying of pineapple. The pretreatment did not significantly increase the drying rate. Drying temperature and ultrasound application accelerated the drying process. Both variables reduced internal and external mass transport resistance. The pretreatments increased the external mass transport resistance during drying.